Deletion of P58IPK, the Cellular Inhibitor of the Protein Kinases PKR and PERK, Causes Bone Changes and Joint Degeneration in Mice - Gilbert, Sophie J.; Meakin, Lee B.; Bonnet, Cleo S.; Nowell, Mari A.; Ladiges, Warren C.; Morton, John; Duance, Victor C.; Mason, Deborah J. (Frontiers in Endocrinology, 2014)
Objective. Protein kinase-like endoplasmic reticulum kinase (PERK) and protein kinase R (PKR) are implicated in endoplasmic reticulum stress-induced arthritis and pro-inflammatory cytokine-mediated cartilage degradation in vitro, respectively. We determined whether knockout of the cellular inhibitor of PERK and PKR, P58IPK causes joint degeneration in vivo and whether these molecules are activated in human osteoarthritis. Materials & Methods. Sections of knee joints from P58IPK-null and wild-type mice aged 12-13 and 23-25 months were stained with Toluidine blue and scored for degeneration using the OARSI system. Bone changes were assessed by radiology and high-resolution micro-computed tomography of hind limbs. Sections from the medial tibial plateaus of two human knees, removed in total knee replacement surgery for osteoarthritis, were immunolabelled for phosphorylated PERK and PKR and P58IPK. Results. Knockout mice exhibited narrower tibiae (p=0.0031) and smaller epiphyses in tibiae (p=0.0004) and femora (p=0.0214). Older knockout mice had reduced total volume inside the femoral periosteal envelope (p=0.023), reduced tibial (p=0.03) and femoral (p=0.0012) bone volumes and reduced femoral bone volume fraction (p=0.025). Compared with wild types, younger P58IPK null mice had increased OARSI scores in medial femoral condyles (p=0.035). Thirty four percent of null mice displayed severe joint degeneration with complete articular cartilage loss from the medial compartment and heterotopic chondro-osseous tissue in the medial joint capsule. Phosphorylated PERK and PKR were localised throughout human osteoarthritic tibial plateaus but in particular in areas exhibiting the most degeneration. There was limited expression of P58IPK. Conclusion. This study is the first to reveal a critical role for P58IPK in maintaining joint integrity in vivo, implicating the PKR and PERK stress signalling pathways in bony changes underlying the pathogenesis of joint degeneration.